Low level treadmill testing of 50 patients with acute myocardial infarction prior to discharge from hospital - nntowon, Nabil A.; AL-hamdi, Amar T.; Hassan, Hakema S. (Journal of the Faculty of Medicine Baghdad, 2005)
Objectives: (I) to describe the hemodynamic and electrocardiograph (ECG) responses in patients with acute myocardial infraction (AMI) to a low level treadmill test (2) to assess the safety of low-level treadmill testing after AMI (3) to determine if information gained from the test can be used for discharge planning.Methods: 50 consecutive patients with AMI were subjected for symptoms limited treadmill testing in the CCU of University Teaching Hospital Iraqi medical College, their age range was from 30-70 with mean age of 55 years. Blood pressure, heart rate, and ECG during a low level treadmill test studied 6 days after AML They were divided into two groups, group I those who could finish the test and group 2 those who couldn't finish the test.Results: 38 patients (76 percent) completed the test. Fatigue was the main reason for the early stopping of the test. Between the rest and maximum exercise there was 12% increase in systolic blood pressure, 6 percent increase in diastolic blood pressure and 17 percent increase in heart rate. The resting systolic blood pressure, diastolic blood pressure and heart rate were significantly increased (p I mm was seen in 5 patients.Conclusions: This low level treadmill testing was safe if it is done under supervised conditions. It provides an objective information about the patient’s readiness for discharge and a help in future management of the patients.